Advantages of Raising Teak (Tectona grandis) Plantations by Using Root Trainer Plants - Khedkar, M. H. (Indian Forester)
The trial of raising Teak (Tectona grandis) plantation by using root trainer plants has shown interesting performance. Due to development of multiple tap roots, the growth of root trainer Teak plants will be better and faster as compared to stump plant. This technology will help in better establishment of Teak plantations.